PENINGKATAN KREATIVITAS KERJA MELALUI PENGUATAN KEPRIBADIAN DAN IKLIM ORGANISASI PADA GURU HONORER DI SMA NEGERI - Mulyadi .; Griet Helena Laihad; Hari Muharam (JURNAL MANAJEMEN PENDIDIKAN, 2020)
IMPROVING STATE SENIOR HIGH SCHOOL HONORARY TEACHERS CREATIVITY THROUGH PERSONALITY STRENGTHENNING AND ORGANIZATIONAL CLIMATEThe creativity of teachers is one important aspect that determines the success of achieving goal of education that is for the building up the intellectual life of the nation. The study is intended to find out the efforts needed to improve the creativity of teachers through personality and climate of the organization of honorary teachers of SMA Negeri at Cibinong, Bogor District. This research is utilizing correlation methods of research, where the first phase of the research was carried out by using a method of quantitative and the data collected through the deployment of questionnaires, and then analyzed by using regression and supported by the description of the statistics. Population of the research were 174 honorary teachers of SMA negeri at Cibinong district. The sample study as many as 122 respondents were determined by the Taro Yamane formula that using the method of proportional random sampling. The results of the quantitative study revealed that personality which emphasizes the stability of emotions (emotional stability), openness (extroversion), easily agreed (agreeableness), can be relied upon (conscientiousness) and openness to experience may contribute to improve creativity. While organizational climate that emphasizes the responsibility of a member, the structure of the organization, award, standards of performance and working environment can contribute to improve creativity. Based on the findings, it is concluded that the stronger of personality and organizational climate, the higher creativity will be.